(untitled) (Med Phoenix, 2018)
Background: Birth preparedness and complication readiness is a key component of globally accepted safe motherhood programs that can reduce the number of women dying from the obstetrical complication. Methods: A descriptive cross sectional study was carried out to assess the knowledge and practice regarding birth preparedness and complication readiness (BPACR) among antenatal mothers attending obstetric and gynecological Department of National Medical College and Teaching Hospital (NMCTH), Birgunj, Parsa, Nepal. Total 60 antenatal mothers were selected using non probability purposive sampling technique. The obtained data was analyzed by descriptive analysis- frequency, percentage, mean, standard deviation and inferential statistics by using Karl Pearson’s coefficient correlation and Chi-square. Results: The findings of the study revealed that 63.33% of antenatal mothers were in the age group 20-24 years, 53.33% were hindu by religion, 85% from rural area, less than half 43.33% were illiterate, most of them 91.66% were housewife, majority of their husbands occupation was service 71.67%, about 36.67% of them had been one time pregnant and majority of antenatal mothers 66.67% had received information regarding BPACR from health personnel. The study identified only 50% of the antenatal mothers had moderate knowledge and 83.33% had poor practice of preparation for birth and its complication. Conclusions: Thus the study concluded that antenatal mothers had inadequate knowledge and poor practices and these are not associated with any socio-demography components except knowledge is found associated with occupation. Med Phoenix. Vol. 3, Issue. 1, 2018, Page: 16-20